Summary of the Workshop to Identify Gaps and Possible Directions for NASA's Meteoroid and Orbital Debris Programs (National Academies Press, 2011)
"A Summary of the Workshop to Identify the Gaps and Possible Directions for NASA's Micrometeoroid and Orbital Debris Programs summarizes the two-day workshop held on March 9-10, 2011, where various stakeholders presented diverse perspectives on matters concerning NASA Micrometeoroid and Orbital Debris (MMOD) programs, NASA mission operators, the role and relationships of NASA MMOD programs to other federal agencies, MMOD and the commercial industry, and orbital debris retrieval and removal. The report assesses NASA's existing efforts, policies, and organizations with regard to orbital debris and micrometeoroids by creating advisory dialogue on potential opportunities for program enhancement and maintenance practices."--Publisher's description.